DAMPAK PSIKOLOGI MAKIAN BAHASA INDONESIA DITINJAU DARI STRATA SOSIAL MASYARAKAT BAHASA - Arfan Rauf (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2017)
This study was an observational research that starts from planning, implementing, and drawing conclusions. The research subjects were people who lived in Tamalatea Village, Makassar City, South Sulawesi, based on Social strata as many as 15 people. Data collection techniques were observation, tapping, fishing line, see, note, and record. All data obtained were analyzed through stages (1) grouping similar data, (2) reading the data as a whole, (3) analyzing data with the method of